Correlation Ship between Some Hematological Parameters and Smoking for Students - Manar Kareem Alquraishy1 , Alia Hussein Al-Mousawi1, Ahmed Adnan AL-Khafagi2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
This study including collected 172 blood sample from AL-Kafeel University college, these samples including102 sample to male and 70 sample for female in which students samples were 53 for smoker and 119 nonsmoker , to evaluate some of parameters such as ABO , RH , blood pressure and clotting time .The results showed blood group A+ was more frequent which represent 33.7 % followed by O+ blood groupwhich represent 25.6% while B- was the last ,in other results displayed AB- and RH + was more frequent thanRH -. Systolic and diastolic pressure examined was demonstrated there were mild hypertension in bloodpressure between samples of studied, while result gloating time was exhibited range 30 sec to 3 minute .